Sources and atmospheric processing of size segregated aerosol particles revealed by stable carbon isotope ratios and chemical speciation. (September 2018) - Masalaite, A.; Holzinger, R.; Ceburnis, D.; Remeikis, V.; Ulevičius, V.; Röckmann, T.; Dusek, U.
Abstract: Size-segregated aerosol particles were collected during winter sampling campaigns at a coastal (55°37′ N, 21°03′E) and an urban (54°64′ N, 25°18′ E) site. Organic compounds were thermally desorbed from the samples at different temperature steps ranging from 100 °C to 350 °C. The organic matter (OM) desorbed at each temperature step is analysed for stable carbon isotopes using an isotope ratio mass spectrometer (IRMS) and for individual organic compounds using a Proton Transfer Reaction Time-of-Flight Mass Spectrometer (PTR-MS). The OM desorbed at temperatures <200 °C was classified as less refractory carbon and the OM desorbed at temperatures between 200 °C and 350 °C was classified as more refractory carbon. At the coastal site, we identified two distinct time periods. The first period was more frequently influenced by marine air masses than the second time period, which was characterized by Easterly wind directions and continental air masses. During the first period OM contained a large fraction of hydrocarbons and had a carbon isotopic signature typical of liquid fossil fuels in the region. Organic mass spectra provide strong evidence that shipping emissions are a significant source of OM at this coastal site. The isotopic and chemical composition of OM during the second period at the coastal site was similar to the composition at the urban site. There was a clear distinction in source contribution between the less refractory OM and the more refractory OM at these sites. According to the source apportionment method used in this study, we were able to identify fossil fuel burning as predominant source of the less refractory OM in the smallest particles (D50 < 0.18 μm), and biomass burning as predominant source of the more refractory OM in the larger size range (0.32 < D50 < 1 μm). Graphical abstract: Image 1 Highlights: Biomass burning is the predominant source of the more refractory carbonaceous aerosol at particle sizes >340 nm. Fossil fuel burning was identified as predominant source of the less refractory fraction for <180 nm particles. Heavy fuel exhaust emissions from ships can enhance OC concentrations at the coastal site. Abstract : Chemical and isotopic analysis of carbonaceous aerosol particles revealed a clear distinction in source contribution at coastal and urban sites.